Retinal axon guidance: novel mechanisms for steering - van Horck, Francis PG (2004)
Axons from the retina traverse different molecular territories as they navigate to the tectum. A single territory might span only a few cell diameters and harbour multiple guidance cues, many of which are beginning to be characterized. Also present in the pathway are ‘modulators’ that influence a growth cone’s response to a coincident signal but do not guide growth directly. An emerging principle is that the growth cone, itself, changes molecularly as it journeys through the visual pathway. Growing retinal axons contain mRNAs, ubiquitinating and apoptotic enzymes, translation and degradation machinery. Guidance cues can trigger rapid and local synthesis, degradation and endocytosis of proteins, providing a fast and flexible way for growth cones to respond to cues in their microenvironment and to alter their responsiveness. The data raise the idea that the localized synthesis and downregulation of proteins might help to steer retinal axon growth and, further, might contribute to the changing character of a growth cone as it ages.